Construindo marcas de resiliência: a prática humanizada do Serviço Social - Bittencourt, Liane (2016)
Resilience has been a theme increasingly recurring in a time in which exceptional ocurrences reach a great number of people. On the other hand, our everyday life imposes restrictive measures contributing to the worsening of social inequality. In this scenario, the professionals of Social Service and their competencies starts being in evidence so that, they can tackle such adverse circumstances. This paper aims at arguing that in their daily activities, the Social Service workers are not only based on humanistic principles. They are also ethically commited in a way of promoting the life as a right. The Social Service professionals are being identified as Resilience tutors to be in charge of changing the reality of each individual being and themselves, as well as, small groups and territories. Besides, by considering the changing either in the concepts and polices that regulate their profession, we argue it would be possible to align this subject to Resilience concepts. This study aims at identifying the reference marks of resilience disposed in the social structure as a result of political actions that may be able to create a way out to confront the adversities having as focus the comprehension of the subjectivity and its value as the primary driver of this dynamic. As of a qualitative nature held in two steps, his study was proposed as following: the first took Likert scale into account , and the second, a group discussion. This research aims at facilitating the approach and the appropriation of the concept of Resilience by the Social Service workers in a way it could broad their knowledge as a key to a better understanding of the theme as well as their professional expertise